Gender, competition, and performance: Evidence from chess players - Peter Backus; Maria Cubel; Matej Guid; Santiago Sanchez-Pages; Enrique López Ma\~nas (Quantitative Economics, 2023)
This paper studies gender differences in performance in a male-dominated competitive environment chess tournaments. We find that the gender composition of chess games affects the behaviors of both men and women in ways that worsen the outcomes for women. Using a unique measure of within-game quality of play, we show that women make more mistakes when playing against men. Men, however, play equally well against male and female opponents. We also find that men persist longer before losing to women. Our results shed some light on the behavioral changes that lead to differential outcomes when the gender composition of competitions varies.
Keywords: D03; J16; J24; J70; L83; M50; 330; Competition; gender; chess